Spearfishing-induced behavioral changes of an unharvested species inside and outside a marine protected area. Issue 1 (10th February 2016) - Tran, Diem Samantha C.; Langel, Katharine A.; Thomas, Madison J.; Blumstein, Daniel T.
Abstract: By prohibiting fishing, marine protected areas (MPAs) provide a refuge for harvested species. Humans are often perceived as predators by prey and therefore respond fearfully to humans. Thus, fish responses to humans inside and outside of an MPA can provide insights into their perception of humans as a predatory threat. Previous studies have found differences in the distance that harvested species of fish initiate flight (flight initiation distance—FID) from humans inside and outside an MPA, but less is known about unharvested species. We focused on whether the lined bristletooth Ctenochaetus striatus, an unharvested surgeonfish, can discriminate between a snorkeler and a snorkeler with a spear gun inside and outside of a no-take MPA in Mo'orea, French Polynesia. Additionally, we incorporated starting distance (the distance between the person and prey at the start of an experimental approach), a variable that has been found to be important in assessing prey escape decisions in terrestrial species, but that has not been extensively studied in aquatic systems. Lined bristletooth FID was significantly greater in the presence of a spear gun and varied depending on if the spear gun encounter was inside or outside of the MPA. These results imply a degree of sophistication of fish antipredator behavior, generate questions as to how a nontargeted species of fish could acquire fear of humans, and demonstrate that behavioral surveys can provide insights about antipredator behavior.